2011
DOI: 10.1016/j.ijid.2010.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel markers for uncomplicated lower genital tract infections and upper genital tract pathology due to Chlamydia trachomatis

Abstract: The use of these assays could potentially facilitate earlier diagnoses in women suffering UGT pathology due to C. trachomatis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…P-type ATPases constitute a superfamily of cation transport enzymes that mediate transmembrane exchange of all biologically significant cations [27]. In contrast, HSP70 is associated with outer membrane complexes of EBs and was originally thought to play a role in either attachment or entry of the EB into host cells [28, 29]. It is suggested that HSP70 indeed confers a humoral antibody response.…”
Section: Resultsmentioning
confidence: 99%
“…P-type ATPases constitute a superfamily of cation transport enzymes that mediate transmembrane exchange of all biologically significant cations [27]. In contrast, HSP70 is associated with outer membrane complexes of EBs and was originally thought to play a role in either attachment or entry of the EB into host cells [28, 29]. It is suggested that HSP70 indeed confers a humoral antibody response.…”
Section: Resultsmentioning
confidence: 99%
“…Still, studies evaluating the diagnostic potential of the Medac cHSP60 ELISA test have revealed conflicting results, thus the ability of this assay to distinguish various C. trachomatis disease stages may be limited [ 169 , 170 ]. Australian study by Collet et al demonstrated that the use of four chlamydial antigens (CT157, CT423, CT727, and CT396) could potentially facilitate earlier diagnoses in women suffering from tubal occlusion and other pathologies of the upper genital tract [ 171 ]. They were found to be capable of discriminating between the infection and disease sequelae, such as tubal infertility.…”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…Current research [34] involves the evaluation of chlamydial antigens (CT157, CT423, CT727, and CT396) to help in differentiation between lower genital infection and upper genital disorder from C. trachomatis. A number of potential markers for PID are under research, including pentraxin 3, E-cadherin, myeloperoxidase, stromal cell-derived factor 1, and the matrix metalloproteinase-9/matrix metalloproteinase-2 ratio [35 & ].…”
Section: Diagnosismentioning
confidence: 99%